Procedural Justice, Compliance and The ‘Upstanding Citizen’: A Study of Community Protection Notices - Black, Alex (The British journal of criminology, 2022)
This article explores procedural justice and motivational postures theories through the lens of Community Protection Notices (CPN), civil measures used to tackle anti-social behaviour in England and Wales. Through a qualitative study of CPN recipients, this article adds to our understanding of the social identity aspect of procedural justice theory by examining the impact on self-identified ‘upstanding citizens’ issued with a CPN for behaviours that they disputed on moral grounds. In order to renegotiate this anti-social label, participants explored other social categories to create distance between themselves and the authorities and challenged their role as representatives of the ‘law-abiding majority’. Ultimately, participants felt ‘compelled’ to comply with the requirements of their CPN, which in turn damaged perceptions of legitimacy.